PENGEMBANGAN MODEL PEMBELAJARAN AKTIF BERBASIS INKUIRI (ABI) UNTUK MENGEMBANGKAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA - Saiful Prayogi; Muhali Muhali (IKIP Mataram, 2015)
The purpose of this research was to develop an inquiry base active (IBA) learning model to develop students' critical thinking skills. Inquiry was chosen as the base for the development of the model, because according to Arends (2012) the inquiry learning model was developed for the purpose of how learners think, in this case including critical thinking. Elements of critical thinking skills developed, namely interpretation, analysis, evaluation, inference, explanation and self-regulation. The IBA learning model was based on scientific inquiry activities, thus indirectly practicing scientific process skills on students. In general, the validator assessment of the developed learning model was valid with the score range 4 to 4.56. The conclusion of the validity test of this learning model was the inquiry based active learning model valid and proper to be used as a reference to develop the learning device and implemented / experimented to develop students' critical thinking skill.